PENGARUH KOMPETENSI APARATUR DESA, KOMITMEN PADA TUGAS DAN REGULASI TERHADAP PENGELOLAAN KEUANGAN DESA DI KABUPATEN BOMBANA - Elfin, .; wawo, Andi Basru; Husin, . (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This research aims to examine and analyze the influence of village apparatus competencies, commitment to tasks, and regulations on village financial management in Bombana . Respondents in this research were village financial managers based on Permendagri Number 113 of 2014 consisting of Village Heads as holders of village financial management power and technical implementers of village financial management (PTPKD) which consisting of Village Secretaries, Section Chief / Financial Chief and Treasurer. The total respondents were 139 people. The data analysis which were used in this resears is multiple linear regression analysis techniques.  The results of the research shows that (1) the competence of village officials has no significant effect on village financial management, (2) commitment to the task has a significant effect on village financial management, (3) regulation has a significant effect on village financial management.  Keywords :  Village Apparatus Competence, Commitment To Duties,  Regulations, Village Financial Manajemen